2017
DOI: 10.19150/me.7746
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of airborne float coal dust emitted during continuous mining, longwall mining and belt transport

Abstract: Float coal dust is produced by various mining methods, carried by ventilating air and deposited on the floor, roof and ribs of mine airways. If deposited, float dust is re-entrained during a methane explosion. Without sufficient inert rock dust quantities, this float coal dust can propagate an explosion throughout mining entries. Consequently, controlling float coal dust is of critical interest to mining operations. Rock dusting, which is the adding of inert material to airway surfaces, is the main control tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The dust concentration and distribution ( Fig. 2 ) for this study were similar to the levels observed in the field [ 16 – 18 ].…”
Section: Methodssupporting
confidence: 84%
“…The dust concentration and distribution ( Fig. 2 ) for this study were similar to the levels observed in the field [ 16 – 18 ].…”
Section: Methodssupporting
confidence: 84%
“…This dust concentration was similar to the levels observed during a longwall survey conducted by NIOSH researchers. [35]…”
Section: Methodsmentioning
confidence: 99%
“…The threshold of 20 μm represents the 98 th percentile of lognormal distribution that fits the frequency histogram for particles greater than 4 μm, and matches the 50% cut point of an airborne dust sampling cyclone used during NIOSH FCD field surveys. [35] The final bin contains the remaining and largest particles that were measured during testing.…”
Section: Methodsmentioning
confidence: 99%
“…NIOSH conducted sampling in the return on a continuous miner section, on a longwall face, and in a belt entry with two transfer points to quantify float and respirable dust levels [Shahan et al 2017]. The continuous mining section was using exhausting face ventilation developed with tubing and an auxiliary fan located in the return.…”
Section: Float Dust Control Technologiesmentioning
confidence: 99%